Composition, valence and oxygen reduction reaction activity of Mn-based layered double hydroxides. Issue 2 (3rd April 2019) - Iwai, Yu; Miura, Akira; Rosero-Navarro, Nataly Carolina; Higuchi, Mikio; Tadanaga, Kiyoharu
ABSTRACT: The oxygen reduction reaction (ORR) activity and cation valences of Mn-based Ni–Mn–Fe and Mg–Mn layered double hydroxides (LDHs) with various compositions were studied. The valences of the 3D transition metals (Mn, Fe, and Ni) were examined by X-ray absorption. The average valence of Ni was approximately 2, and that of Mn was approximately 3 in the LDHs investigated in this study. The valence of Fe decreased with increases in the Mn/Fe ratio. Increasing the amount of Mn enhanced the ORR activity, while the valences and surface areas of the LDHs had no significant effect on the activity.